The Correlation of Attractiveness BNI’s Sponsorship to Chelsea FC and Affiliate Group with Interest in The Use Of Service - Soffa Wicaksono, Muhammad; Setyabudi, S.Sos, MM, Djoko (Interaksi Online, 2017)
Sponsorship as a marketing program is expected to help build a positive image to enhance the financial benefits of a company. Bank Negara Indonesia or BNI use this channel to be the official sponsor of Chelsea FC to build awareness and brand image to continue to compete in the world of banking. This study aims to determine the Correlation of Attractiveness BNI’s Sponsorship to Chelsea FC and affiliate groups with interest in the use of services. The theory used in this study is Information Integration Theory, and the Cognitive Learning Theory. Sampling technique were used is Non-Probability Sampling is that purposive sampling. Respondents in this study are those who have not used the services of BNI, have a favorite football club and diligently follow the latest news about football least once a week. Analysis Kendall correlation test is used to test the hypothesis. The results of this study indicate that there is no correlation between attractiveness BNI’s sponsorship to chelsea fc and interest in the use of services, where the significance value as big as 0.966. Furthermore, there is a weak correlation between the affiliate group and interest in the use of services, where the significance value as big as 0.022 and a correlation coefficient as big as 0,207. Then, this study provides advice to Bank Negara Indonesia to establish close cooperation with the parties or have close connection with BNI products, such as for example by working with Indonesian public figure is more familiar with the Indonesian community. And then the sponsorship events should be pack in communicative way